Effects of inspiratory muscle training in older adults - Seixas, Mariana B. (2020)
BACKGROUND: Inspiratory muscle training (IMT) has been widely applied to different populations, including the general population of older adults. In addition to increasing inspiratory muscle strength, other benefits of IMT in the health of this population have been reported. The primary aim of this study was to review the effects of IMT on the general parameters of health (eg, respiratory, functional, physical, and other variables) in older adults (≥ 60 y), and the secondary aim was to analyze the main IMT protocol used in the studies. METHODS: We searched the MEDLINE, PEDro, SciELO, and LILACS databases to identify relevant randomized controlled clinical trials, and we assessed their methodological quality according to the PEDro scale. The Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) guidelines were used to guide the development of the protocol for this systematic review. RESULTS: The search yielded 7 studies involving 248 participants from 917 ti-tles. The main outcomes investigated in response to IMT were related to the respiratory, functional, and physical variables. The results indicate that IMT promotes an increase of inspiratory muscle strength and diaphragmatic thickness in older adults. There was heterogeneity in the protocols described for this population with respect to the total training time (4–8 weeks), intensity (30–80% of the maximum inspiratory pressure), and weekly frequency (5 or 7 sessions). CONCLUSIONS: The reviewed studies revealed a positive trend for the effectiveness of IMT in improving inspiratory muscle performance in elderly subjects. More randomized studies are needed to evaluate other outcomes (eg, functional ca-pacity, exercise capacity, cardiac autonomic control, quality of life, and others) to provide robust evidence that this training modality can promote improvements in health parameters in this population. In addition, the usual IMT prescription in this population is based on sets and repetitions, of mild to moderate intensity, performed on most days of the week, for ≥ 4 weeks.